The behavioral driving mechanism of ecological co-management among multiple subjects from the perspective of social network embedding: Evidence from coffee-producing areas in China - Xiumei Xu; Dengke Wang (PLoS ONE, 2026)
The coffee-growing areas in the Gaoligong Mountains of China face ecological challenges including soil erosion and water pollution from traditional processing methods. To analyze the drivers of stakeholder participation in addressing these issues, this study integrates the Theory of Planned Behavior (TPB) and Social Network Embeddedness Theory (SNET), which together explain how individual cognitions and social structures shape cooperative behavior. Data from a stratified survey of 137 stakeholders were analyzed using PLS-SEM. The results demonstrate that (1) Both emotional networks (ENW) and suggestive networks (SNW) have significant direct effects on participation intention. (2) Indirectly, ENW enhances intention by strengthening individual behavioral attitude, subjective norm, and perceived behavioral control through emotional bonds and identity. (3) SNW improves intention primarily by boosting perceived behavioral control through information dissemination. And (4) the core TPB constructs (attitude, norm, control) are confirmed as key mediators. This paper contributes a validated integrated framework that elucidates the social-psychological pathways for fostering effective ecological co-management.